Physiotherapeutic approachs and resources in the Home Attention Service (HAS) of the Better at Home Program: integrative literature review: integrative review (Research, Society and Development, 2023)
This integrative review study aimed to describe the physical therapy approaches and resources in the SAD of the Better at Home Program. The search for data was conducted in the PubMed, Biblioteca virtual em saúde (BVS), Literatura Latino-americana e do Caribe em Ciências da Saúde (LILACS), SCIELO and Google acadêmico databases with the descriptors: Physiotherapy, Home Treatment, Home Care Service, Home Care, and using strategies for combining the terms. The screening of the articles found was done by reading the title, reading the abstract, and, still in case of doubt, the article was read in full and selected by the inclusion and exclusion criteria. After filtering and analyzing the publications, 8 articles were selected for this review. It was evident in this review that several are the contexts experienced in the work of the physical therapist in the SAD, and several are the resources used by him, within an important role within the multidisciplinary team. It was also possible to identify the challenges, advances and potentials of this work with patients and home caregivers. The physical therapist in the SAD acts in the context of the child to the elderly, from the patient with pneumofunctional needs to the patient in palliative care, with techniques and resources, either manual, electrical, kinesiotherapeutic, mechanical or orientational. In this scenario, the studies used and the reviewers of this research point to the need for further research on the subject to strengthen evidence-based practice.